Understanding of Glorification toward God through Mullā Ṣadrā’s Commentary on Q.S. al ’aʿlā - Kerwanto Kerwanto (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This article will try to explain Ṣadrā’s views and thoughts contained in one of his monumental work, Tafsīr al Qur’ān al karīm. The main problem which is the object of this research is Sadra's philosophical views and thoughts in Ṣadrā’s interpretation (tafsīr Q.S. al ’aʿlā). This study is an attempt to explore the benefits of these important aspects of religious sources unearthed from the instructions of Qur'an combined with rational principles of philosophical and mystical experiences (intuitive) of Ṣadrā. This study is important because it is till now emerging groups that debating the importance of philosophy. Some groups consider that the philosophical teachings is foreign things and contrary to the teachings of religion, especially to the Qur'an and sunah of the prophet; the notion that between philosophy and the Qur'an have a distance that cannot be put together. Of course, such view is contrary to the views of the Muslim philosophers. The Muslim philosophers believe that between philosophy and revelations (divine laws) are not contradictory. In fact, both have a synergistic relation. Keywords : al mabda’, Ḥikmah Mutaʿāliyah, irfān, Q.S. al ’aʿlā, maʿād, nubuwah, Ṣadrā, tafsīr, tasbīḥ.